1996
DOI: 10.1007/bf01411746
|View full text |Cite
|
Sign up to set email alerts
|

The effects of the pretreatment of intravenous high dose methylprednisolone on Na+-K+/Mg+2 ATPase and lipid peroxidation and early ultrastructural findings following middle cerebral artery occlusion in the rat

Abstract: The sodium-potassium activated and magnesium dependent adenosine-5'-triphosphatase (Na(+)-K(+)/Mg(+2) ATPase EC.3.6.1.3.) activity and lipid peroxidation and early ultrastructural findings were determined in rat brain at the acute stage of ischaemia produced by permanent unilateral occlusion of the middle cerebral artery (MCA). The effects of the pretreatment with intravenous high-dose methylprednisolone (MP) on these biochemical indices and ultrastructural findings were also evaluated in the same model. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 36 publications
2
3
0
Order By: Relevance
“…In the present study, inhibition of Na + /K + -ATPase activity was observed in the early phases following the trauma and remained at a decreased level throughout the first 24 h. A similar result was obtained in the studies of Ildan et al 34 and Jamme et al, 35 in which Na + /K + -ATPase activity diminished within a short period following the focal cerebral ischemia model in rats and remained below the control level over 120 minutes. On the other hand, the inhibition in the Mg 2+ /Ca 2+ -ATPase activity occurred soon after the trauma and became particularly marked at 24 h. This result is in accordance with the study of Parson et al 36 in which the inhibition of microsomal Mg 2+ /Ca 2+ -ATPase activity in rat brain subjected to global ischemia had increased to the maximum level after 60 minutes.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the present study, inhibition of Na + /K + -ATPase activity was observed in the early phases following the trauma and remained at a decreased level throughout the first 24 h. A similar result was obtained in the studies of Ildan et al 34 and Jamme et al, 35 in which Na + /K + -ATPase activity diminished within a short period following the focal cerebral ischemia model in rats and remained below the control level over 120 minutes. On the other hand, the inhibition in the Mg 2+ /Ca 2+ -ATPase activity occurred soon after the trauma and became particularly marked at 24 h. This result is in accordance with the study of Parson et al 36 in which the inhibition of microsomal Mg 2+ /Ca 2+ -ATPase activity in rat brain subjected to global ischemia had increased to the maximum level after 60 minutes.…”
Section: Discussionsupporting
confidence: 92%
“…37,38 Experimental evidence suggests that the plasma membrane enzymes are a target site for neuroactive steroid action; methylprednisolone has been demonstrated to enhance Na + /K + and Mg 2+ -activated ATPase in the focal cerebral ischemia and spinal cord trauma animal models. 24,34 The present study provides evidence that U-83836E given prophylactically, enhances Na + /K + and Mg 2+ /Ca 2+ -ATPase activities, possibly by scavenging iron-catalyzed free radical formation, and inhibiting lipid peroxidation, 9 the latter of which was shown in our previous study. 39 21-aminosteroids have been shown to reduce edema in ischemic and traumatic brain injury, 15,16,40 possibly protecting the BBB from peroxidative damage.…”
Section: Discussionsupporting
confidence: 72%
“…It is well documented that mitochondrial dysfunction associated with the loss of Ca 2+ homeostasis and enhanced cellular oxidative stress has long been recognized to play a major role in cell damage associated with excitotoxicity. Na + , K + ‐ATPase is known to be highly susceptible to free‐radical damage and lipid peroxidation because of its plasmalemmal embedding and its phospholipid requirement for maintenance of activity (Furui et al, 1990; Ildan et al, 1996). Mg 2+ ‐ATPase is also vulnerable to damage by reactive oxygen species.…”
Section: Discussionmentioning
confidence: 99%
“…A marked influx of Ca 2+ into neurones during ischaemia has been shown to provoke catastrophic events, leading to irreversible neuronal injury [23,24]. Additionally, Na + , K + ‐ATPase is known to be highly susceptible to free radical damage and lipid peroxidation due to its plasmalemmal embedding and its phospholipid requirement for maintenance of activity [25,26]. It is therefore proposed that the attenuation by honokiol of decreased Na + , K + ‐ATPase activity in response to ischaemia as described in the present report is due, at least in part, to the antioxidative action of the drug.…”
Section: Discussionmentioning
confidence: 73%
“…The time sequence of reactive oxygen species production during the first day of brain ischaemia, suggests that the machinery of reactive oxygen species formation is still processing in the freshly prepared synaptosomes. Reactive oxygen species is capable of oxidizing proteins, lipids and DNA, and thus alters the conformation and function of proteins; among them, Na + , K + ‐ATPase was found to be the most sensitive to be attacked [25,26]. As discussed above, the mitochondrial damage caused by the reactive oxygen species generated during brain ischaemia contributes to the neuronal cell death observed under this condition.…”
Section: Discussionmentioning
confidence: 99%